(untitled) (Journal of Economics, Law and Society, 2026)
Building resilient companies capable of withstanding financial pressure is increasingly important for stakeholders, especially banks, investors, and suppliers operating in uncertain economic environments. Conventional credit assessment models often prioritize financial ratios, yet overlook the strategic influence of managerial capability on a firm’s capacity to endure stress and maintain financial stability. This research places management efficiency at the forefront as a key driver of corporate resilience, examining how internal resource utilization, operational decisions, and financial management shape long-term sustainability. The analysis is based on 1,531 corporate loan cases from a commercial bank in Bosnia and Herzegovina, incorporating balance sheet and income statement indicators available at loan approval, including both static financial ratios and year-to-year performance changes. Factor analysis and regression results reveal that liquidity, self-financing levels, asset turnover, gross margin, and accounts receivable collection time are relevant predictors of financial resilience; however, management efficiency stands out as the most influential determinant. Firms with inefficient managerial practices demonstrate substantially lower resilience and higher vulnerability to financial deterioration. The findings highlight the strategic importance of integrating managerial effectiveness into risk evaluation frameworks and support the view that strong management is a foundation of corporate resilience in the financial sector.